Left Ventricular Longitudinal Function Assessed by Speckle Tracking Ultrasound from a Single Apical Imaging Plane - Thomas Bagger; Erik Sloth; Carl-Johan Jakobsen (Critical Care Research and Practice)
Background. Transthoracic ultrasonography of the heart is valuable in monitoring and treatment of critically ill patients. Speckle tracking ultrasound (STU) has proven valid in estimating left ventricular systolic deformation. The aims of the study were to compare conventional and automated STU and to determine whether left ventricular systolic deformation could be estimated from one single imaging plane. Methods. 2D-echocardiography cine-loops were obtained from 20 patients for off-line speckle tracking analysis, consisting of manually tracing of the endocardial border (conventional method) or automatically drawn boundaries (automated method). Results. We found a bias of 0,6 (95% CI −2.2−3.3) for global peak systolic strain comparing the automated and the conventional method. Comparing global peak systolic strain of apical 4-chamber cine-loops with averaged Global Peak Strain obtained from apical 4, 2 and long axis cine-loops, showed a bias of 0.1 (95% CI −3.9−4.0). The agreement between subcostal 4-chamber and apical 4-chamber global peak systolic strain was 4.4 (95% CI −3.7−12.5). Conclusion. We found good agreement between the conventional and the automated method. STU applied to single apical 4-chamber cine-loops is in excellent agreement with overall averaged global peak systolic strain, while subcostal 4-chamber cine-loops proved less compliant with speckle tracking ultrasound.